Using remote sensing to map degraded mountain peatlands with high climate mitigation potential in Colombia's Central Cordillera - Battaglia, Michael J.; Lafuente, Angela; Benavides, Juan C.; Lilleskov, Erik A.; Chimner, Rodney A.; Bourgeau-Chavez, Laura L.; Skillings-Neira, Patrick Nicolás (Frontiers in Climate, 2024)
Peatlands are the most carbon-dense ecosystems on earth. In tropical mountains, peatlands are numerous and susceptible to rapid degradation and carbon loss after human disturbances. Quantifying where peatlands are located and how they are affected by land use is key in creating a baseline of carbon stocks and greenhouse gas fluxes from tropical mountain peatlands. However, mapping peatlands in the páramo of the Northern Andes is difficult because they are in a topographically complex environment with nearly continuous cloud cover and frequent conversion to pastures or cropland. Our goal was to identify the different types of páramo peatlands and their degradation patterns on the southern end of the of the Colombian Central Cordillera. Our approach used the spectral responses of optical imagery, temporal variations in ALOS-PALSAR L-band SAR, variation on the Sentinel-1 VV C-band SAR and topography. We used 507 control points across the study area with information on the vegetation and carbon content on the top 20 cm of the soil for 13 land cover classes. Our results show that the use of multiple platforms and dates, and variance of the radar returns is necessary for a clear separation of disturbed and undisturbed peatland classes. Peatland area varied across the study region, covering 7% and 20% of the landscape in the northern and southern portions of the study area respectively. Disturbed peatlands with exotic grasses cover nearly 2% of the area. The overall accuracy of the peatland classes was 82.6%. Our results highlight the prevalence of peatlands in the tropical Andes and a promising approach to detecting peatlands converted to agriculture. Our work will facilitate the restoration and protection of peatlands in the northern Andes, with implications for the future trajectories of the national greenhouse gas inventory.